2013
DOI: 10.1530/edm-13-0042
|View full text |Cite
|
Sign up to set email alerts
|

Benign adrenal adenomas secreting excess mineralocorticoids and glucocorticoids

Abstract: Objective: To recognize that benign adrenal adenomas can co-secrete excess aldosterone and cortisol, which can change clinical management.Methods: We reviewed the clinical and histological features of an adrenal tumor co-secreting aldosterone and cortisol in a patient. Biochemical testing as well as postoperative immunohistochemistry was carried out on tissue samples for assessing enzymes involved in steroidogenesis.Results: A patient presented with hypertension, hypokalemia, and symptoms related to hypercorti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…In the past, cortisol co-secretion in primary aldosteronism has been discussed on the basis of several case studies or case series [9][10][11][12][13][14][15] . Recently, we have investigated a large multi-center cohort of PA patients and revealed that glucocorticoid co-secretion is a phenotype frequently found in PA which might contribute to associated metabolic risks 16 , including a higher risk of cardiovascular events as shown by Nakajima et al 17 .…”
Section: Impaired Glucose Metabolism In Primary Aldosteronism Is Assomentioning
confidence: 99%
“…In the past, cortisol co-secretion in primary aldosteronism has been discussed on the basis of several case studies or case series [9][10][11][12][13][14][15] . Recently, we have investigated a large multi-center cohort of PA patients and revealed that glucocorticoid co-secretion is a phenotype frequently found in PA which might contribute to associated metabolic risks 16 , including a higher risk of cardiovascular events as shown by Nakajima et al 17 .…”
Section: Impaired Glucose Metabolism In Primary Aldosteronism Is Assomentioning
confidence: 99%
“…Subsequently, a steroid metabolome study confirmed that glucocorticoid excess is a frequent finding in PA due to APAs and idiopathic hyperaldosteronism (IHA) and the term ‘Connshing syndrome’ was proposed for this subgroup of patients ( 9 ). These findings suggest that cortisol cosecretion is highly prevalent in patients with PA and it could be the driver for the increased metabolic alterations seen in patients with Conn syndrome ( 1 , 2 , 5 , 6 , 7 , 8 , 9 ). More recently, Gerards et al ( 10 ) performed the 1-mg dexamethasone suppression test, late-night salivary cortisol, and 24-h urinary free cortisol in 161 newly diagnosed patients with PA and found that 77.6% of them had autonomous cortisol secretion as demonstrated by a pathological response in at least one of these screening tests for Cushing’s syndrome.…”
Section: Discussionmentioning
confidence: 88%
“…The latter group, which includes 10–15% of all AAs, comprises adenomas that produce cortisol, aldosterone, or catecholamines. Although aldosterone- and cortisol-cosecreting adrenal adenomas (A/CAAs) were initially thought to be rare, a number of case reports and case series have suggested that this might not be the case ( 1 , 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…These findings might provide a treatment rationale for patients suffering from PA: not only as aldosterone and salt excess increase oxidative stress by themselves but in addition because those patients frequently feature cortisol co-secretion [98,99]. The latter aggravates cardiovascular damage in scenarios with both high and low oxidative stress as glucocorticoid excess impairs the conversion of cortisol to cortisone, leading to glucocorticoid-mediated mineralocorticoid effects even in 11β-HSD2 protected epithelial tissues (▶Table 1) [100][101][102][103][104][105]. As stated previously, changes in redox state may further aggravate glucocorticoid MR agonism.…”
Section: Bowelmentioning
confidence: 99%